Structure–property relationships in polymer-polyols-based polyurethane elastomers - Nabil A. Saleh (1990)
Polyurethanes are a class of materials which can be regarded as filling the gap between rubbery elastomers and rigid plastics and metals. They can exhibit both high elongation and resilience, while retaining high modulus which make them unique for a wide variety of applications in which both stiffness and extensibility is needed. It is now widely accepted that the diverse properties of these copolymers are attributed to the existence of a two phase microstructure. One phase is regarded as a glassy or hard segment, whereas the other phase is considered to be rubbery and to give soft segments. These different segments are known to have glass transition temperatures above roan temperature for the hard segments and below roan temperature for the soft segments. [Continues.]